The dynamic modelling and development of a controller for a general purpose remotely operated underwater vehicle - Finbow, Maximillian (Department of Mechanical Engineering, 2016)
A preliminary mathematical model for the UCT SEAHOG Remotely operated underwater vehicle (ROV) is developed, including estimation of the rigid body, hydrodynamic and hydrostatic properties of the robot. A single state thruster model is developed and verified according to real life test data. A closed-loop speed controller is developed for the thruster module using a standard PI scheme and is implemented on an MSP430 microcontroller using software fixed-point algorithms. The complete ROV system is simulated in Simulink® in an open-loop configuration to gain insight into the expected motion from the vehicle. Controllers for depth and heading holding are designed using standard PID linearized control methods with gain scheduling and are then assessed within the complete system in a simulation environment. In addition, upgrades and maintenance are performed on the Power Pod, light and camera modules. Redesign, manufacture and testing of the SEAHOG junction box is performed, including a design solution to connect the tether power and fibre-optic lines at the surface and on the ROV. An extensive overhaul of the SEAHOG GUI is performed, utilising multicore processing architecture in LabVIEW and resulting in a user-orientated interface capable of controlling and monitoring all existing system data from the robot.